The Importance Of Moral Education In The Formation Of Children's Character - M Zainul Hafizi; Hadi Wiyono (IJGIE (International Journal of Graduate of Islamic Education), 2023)
This study aims to explore the central role of moral education in the process of character formation of children. Through a literature review review, we investigate the basic and theoretical concepts of moral education, as well as its positive impact on children's character development. An in-depth analysis of the literature shows that moral education includes not only moral norms, but also builds ethical values, empathy, and social responsibility. The research also highlights the linkages between moral education, the moral development of individuals, and their contribution to society more broadly. The results of this study are expected to provide a solid theoretical foundation for further understanding of the importance of moral education in shaping children's character.